Impact of Covid-19 on Indian sports league - Singh, A.; Sharma, R. (Social Research Foundation, 2020)
Covid-19 Pandemic has drastically brought down multiple businesses worldwide and others facing numerous challenges to cope up with the current market conditions. It is important, at this time to understand, how one can stabilizes its business and keep learning from the challenges in different markets altogether. There is a drastic impact of Covid-19 Pandemic on different sports leagues in the country India, which too has affected the sports personalities and in large the corporate sponsors of these business models. The successful sports business model of almost all of these sports league in the country had been possible because of the renowned Indian Premier League, which is a premium sports league started in the year 2008, with an intention to bring all the players around the world in India. This would further help to develop the sports leagues and to enhance the revenue through the sponsorship model. This review based paper highlights the problems and challenges faced by the different sports industries and other related businesses in the past. As a result of which, it would help us to learn and strategise to counter such problems with preparedness from the economic and corporate sponsorship point of view.